Application of Stem Cells in Oral Disease Therapy: Progresses and Perspectives - Yang, Bo; Qiu, Yi; Zhou, Niu; Ouyang, Hong; Ding, Junjun; Cheng, Bin; Sun, Jianbo (Frontiers in Physiology, 2017)
Stem cells are undifferentiated and pluripotent cells that can differentiate into specialized cells with a more specific function. Stem cell therapies become preferred methods for the treatment of multiple diseases. Oral and maxillofacial defect is one kind of the diseases that could be most possibly cured by stem cell therapies. Here we discussed oral diseases, oral adult stem cells, iPS cells, and the progresses/challenges/perspectives of application of stem cells for oral disease treatment.